2012
DOI: 10.2174/157341112803216753
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mass Characterization of Glycosaminoglycans with Different Degrees of Sulfation in Bioengineered Heparin Process by Size Exclusion Chromatography

Abstract: Different degrees of glycosaminoglycan sulfation result in their different charge densities. The charge density differences impact their migration behavior in polyacrylamide gel electrophoresis and size exclusion chromatography, two of the most common methods for determining relative molecular masses of polysaccharides. In this study, we investigated the feasibility of using commercially available heparin oligosaccharides as calibrants for measuring the relative molecular masses of intermediates in a bioengine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Although the aforementioned studies clearly demonstrated the value of heparin for growth factor delivery from bioinspired matrices, the attributes of heparin such as the extent of sulfation, pattern of sulfation, molecular weight, and polydispersity of heparin have been less emphasized and not explored in depth [2932]. For example, heparin derivatives with different sulfation patterns differ significantly in their specific binding to VEGF 165 , which affects the subsequent bioactivity of VEGF 165 [24], and desulfated heparin-derivatives lose their stabilizing features and stimulatory capacity [33, 34].…”
Section: 0 Introductionmentioning
confidence: 99%
“…Although the aforementioned studies clearly demonstrated the value of heparin for growth factor delivery from bioinspired matrices, the attributes of heparin such as the extent of sulfation, pattern of sulfation, molecular weight, and polydispersity of heparin have been less emphasized and not explored in depth [2932]. For example, heparin derivatives with different sulfation patterns differ significantly in their specific binding to VEGF 165 , which affects the subsequent bioactivity of VEGF 165 [24], and desulfated heparin-derivatives lose their stabilizing features and stimulatory capacity [33, 34].…”
Section: 0 Introductionmentioning
confidence: 99%
“…The resulting heparosan was >95% pure as determined by nuclear magnetic resonance (NMR) spectroscopy and disaccharide analysis ,. The average molecular weight determined by size‐exclusion chromatography (SEC) was ∼40,000 Da . The purified heparosan was freeze‐dried and stored desiccated at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…The purity of the N ‐acetyl, N ‐sulfoheparosan was determined by NMR spectroscopy and disaccharide analysis , as >95% with 12%–18% N ‐acetyl and 88%–82% N ‐sulfo content. The average molecular weight determined by SEC was 11,000–12,300 Da .…”
Section: Methodsmentioning
confidence: 99%
“…Heparin is the human glycosaminoglycan with the highest degree of sulfation, and one of the few glycosaminoglycans that can contain two or more sulfates on a single monomer. It also has a unique 3-O sulfation which is essential for its strong interaction with antithrombin III [30,31]. Most of the other glycosaminoglycans only have one sulfate group per monomer [31][32][33][34][35].…”
Section: Structure-function Relations Of Sulfated Polysaccharidesmentioning
confidence: 99%
“…It also has a unique 3-O sulfation which is essential for its strong interaction with antithrombin III [30,31]. Most of the other glycosaminoglycans only have one sulfate group per monomer [31][32][33][34][35]. Heparan sulfate, one of the most abundantly expressed glycosaminoglycans that coats virtually every cell surface, has <1 one sulfate per disaccharide unit and does not contain the 3-0 sulfation that is unique for heparin [30,33,34].…”
Section: Structure-function Relations Of Sulfated Polysaccharidesmentioning
confidence: 99%